Perlindungan Hukum Bagi Ahli Waris Terhadap Harta Warisan Yang Beralih Tanpa Persetujuan Ahli Waris - Setio Prabowo; M. Sudirman; Cicilia Julyani Tondy (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2023)
Inheritance occurs when a family member passes away, such as a father, mother, or child, provided that the deceased individual possessed wealth or assets. However, in reality, situations still arise where land rights can transfer through inheritance without involving all heirs in the ongoing transfer process. The research methodology employed in this study is a normative juridical approach. Within this research, the theories of Legal Consequences according to R. Soeroso and Legal Protection according to Satjipto Raharjo are utilized. The research findings indicate that the legal repercussions of transferring inheritance assets without the consent of the heirs, in accordance with the Civil Code, are deemed invalid under the law. The ancestral land is sold by an individual who, in fact, lacks the right to do so, given that the ownership rights to the land actually belong to the heirs. Thus, in accordance with Article 1471 of the Civil Code, the sale transaction becomes null and void.